“Motivation in pre-service English teachers at the technical University of Cotopaxi” - Sandoval Cantuña, Kareliz Abigail (2023)
Nowadays, English has become a universal language, which has forced more people, especially young students, to learn it to achieve personal, better academic, and work opportunities. So, if people want to learn a second language like English, it is necessary to have a good level of motivation. Motivation is a fundamental and relevant component in this process because it directs students to make a substantial effort to commit to their goal of learning the target language. Therefore, this descriptive quantitative study aims to investigate the level and type of motivation at the Technical University of Cotopaxi located in the province of Cotopaxi, Pujilí Canton, Latacunga. The instrument used for data collection was a standardized questionnaire adapted from the Attitude/Motivation Test Battery (AMTB), designed by Gardner, with a 6-point Likert scale adapted from the original 7-point scale. The main objective of this questionnaire was to collect information on student motivation and consisted of three principal parts: four demographic questions, 13 on integrative motivation, and ten on instrumental motivation. The participants were 191 students of the first four semesters of the Pedagogy of National and Foreign Languages career during the academic period of April - August 2022, from which a sample of 162 students was obtained. Data were collected and analyzed using the Statistical Package for Social Sciences (SP SS) and EXCEL. The results showed that all students have a high-level of motivation in English language learning. Moreover, the data indicated that students have a tendency towards integrative motivation than instrumental one. That is because the students' interests are based on having close contact with the culture of native people and being able to communicate effectively using the target language (English). Finally, the results will allow English teachers to consider the level and type of motivation students have in their teaching process. Thus, the teachers will apply didactic and innovative strategies to maintain and increase the students' motivation level within the teaching-learning process of English.